Pelatihan dan Implementasi Aplikasi Retensi Rekam Medis di Klinik Pratama Prima Husada Bandung - Wirahadi, Umar; Setiatin, Sali; Yunengsih, Yuyun; Prakarsa Al Qadr Saleh, Muhammad; Arif Setyawan, Adhita; Dewi, Sofia (PADMA, 2024)
The training and implementation of the medical record retention application at Klinik Pratama Prima Husada Bandung aim to enhance the efficiency of medical record document management in accordance with applicable regulations. The application is designed to support the selection, transfer, and disposal of medical record documents based on the specified retention period, thereby reducing the accumulation of physical documents and expediting information access. The training activities involved healthcare workers and administrative staff, covering topics such as the introduction of medical record retention concepts, application usage, and document management simulations. The implementation results showed that the application improved accuracy in categorizing documents into active and inactive groups and enhanced efficiency in retrieving required documents. Furthermore, the application ensured compliance with regulations related to medical record management. With the success of this training and implementation, Klinik Pratama Prima Husada Bandung is expected to improve the quality of medical record management, support digital transformation, and provide better-organized healthcare services to patients. Among the 20 participants, 5 (25%) were highly proficient, 5 (25%) were moderately proficient, and 10 (50%) were proficient.